A porous, electrically conductive hexa-zirconium(iv) metal–organic framework. Issue 19 (19th April 2018) - Goswami, Subhadip; Ray, Debmalya; Otake, Ken-ichi; Kung, Chung-Wei; Garibay, Sergio J.; Islamoglu, Timur; Atilgan, Ahmet; Cui, Yuexing; Cramer, Christopher J.; Farha, Omar K.; Hupp, Joseph T.
Abstract : Electrical conductivity is engendered in a pyrene containing hexa-zirconium(iv ) metal–organic framework by physically encapsulating fullerenes within MOF cavity. Abstract : Engendering electrical conductivity in high-porosity metal–organic frameworks (MOFs) promises to unlock the full potential of MOFs for electrical energy storage, electrocatalysis, or integration of MOFs with conventional electronic materials. Here we report that a porous zirconium-node-containing MOF, NU-901, can be rendered electronically conductive by physically encapsulating C60, an excellent electron acceptor, within a fraction ( ca. 60%) of the diamond-shaped cavities of the MOF. The cavities are defined by node-connected tetra-phenyl-carboxylated pyrene linkers, i.e. species that are excellent electron donors. The bulk electrical conductivity of the MOF is shown to increase from immeasurably low to 10 −3 S cm −1, following fullerene incorporation. The observed conductivity originates from electron donor–acceptor interactions, i.e. charge-transfer interactions – a conclusion that is supported by density functional theory calculations and by the observation of a charge-transfer-derived band in the electronic absorption spectrum of the hybrid material. Notably, the conductive version of the MOF retains substantial nanoscale porosity and continues to display a sizable internal surface area, suggesting potential future applications that capitalize on the ability of the material to sorb molecular species.